Adipura: Good Environmental Governance Perspective and Fiscal Challenges - Permanasari, Tyasning; Salman, Radian (RSF Conference Series: Business, Management and Social Sciences, 2024)
The research emphasizes the effectiveness of Adipura as an instrument for monitoring the performance of local governments in waste management from the perspective of good environmental governance. Focus study on public participation and fiscal challenges. This is a qualitative research. The main data source from the National Waste Management Information System (NSWMIS) and in-depth interviews with central and local government, members of the Adipura Advisory Board, and the communities. Also supported by secondary data relevant to the study. The purpose of research are to determine the extent of the effectiveness of Adipura and to analysis the factors that must be improved to increase its effectiveness. The results indicate that the placement of Adipura as an instrument for monitoring the performance of regional waste management is appropriate, but still needs to be improved because the impact of Adipura has not been maximized in encouraging sustainable waste management in the region. It is necessary to recalculate the components and subcomponents of Adipura, by adding Non-Physical Components, increasing the portion of public participation and fiscal support for waste management.